Students’ Social and Emotional Competence Promoting Positive Social Relationships and Skills - Koizumi, Reizo; Yamada, Yohei (International Journal of Criminology and Sociology, 2016)
The current study examined causal relationships between social and emotional competence and social relationships and skills in the classroom. Participants were 2,410 third- to ninth-grade students and they responded to the scales of social and emotional competence (SEC), self-esteem, and normative behavior. The classroom teachers rated their normative behavior in the classes. The results indicated that perceived SEC has influences on children's actual normative behavior through self-esteem and perceived normative behavior, and that self-esteem partly mediates the cause-and-effect process between perceived SEC and perceived normative behavior. The same causal structure was found among both elementary school students (third to sixth grades) and junior high school students (seventh to ninth grades), with age-related differences in some path coefficients. The findings support that SEC enhancement by social and emotional learning brings positive outcomes in students' perception and social relationships and skills.